Warm Compress for Elderly with Gout Arthritis: Case Study - Nurhidayah, Gina; Puspita, Tantri (CV. Literasi Publikasi Indonesia, 2023)
The disease known as Gouty Arthritis, or simply Gout, is a condition that affects the joints due to an interference in metabolism, particularly the metabolism of purines, leading to high levels of uric acid in the blood. Elevated levels of uric acid can cause the formation of crystals in the joints and surrounding tissues, resulting in severe pain and potential damage to the joints. In the context of caring for elderly patients with Gouty Arthritis, a study involving warm compress therapy was conducted at the Orchid Griya Elderly in Garut Regency. The study utilized a descriptive case study approach, involving history taking, observation, physical examination, and medical notes. The participants were elderly patients with Gouty Arthritis who received warm compress therapy. The results of the study indicated that the main nursing problem, chronic pain, was effectively addressed through warm compress interventions based on Evidence Based Practice. The analysis revealed a decrease in the intensity of gouty arthritis pain with the use of warm compress therapy, suggesting that this approach can effectively increase blood flow to the affected area and accelerate the healing process.